Selected Topics in Homogenization of Transport Processes in Historical Masonry Structures - Sykora, Jan; Zeman, Jan; Ŝejnoha, Michal (The open civil engineering journal, 2012)
The paper reviews several topics associated with the homogenization of transport processed in historical ma-sonry structures. Since these often experience an irregular or random pattern, we open the subject by summarizing essen-tial steps in the formulation of a suitable computational model in the form of Statistically Equivalent Periodic Unit Cell (SEPUC). Accepting SEPUC as a reliable representative volume element is supported by application of the Fast Fourier Transform to both the SEPUC and large binary sample of real masonry in search for effective thermal conductivities lim-ited here to a steady state heat conduction problem. Fully coupled non-stationary heat and moisture transport is addressed next in the framework of two-scale first-order homogenization approach with emphases on the application of boundary and initial conditions on the meso-scale.